Environmental Impact: QAnon and Media Ecology - Clements, Joshua Grant (My University, 2021)
This thesis studies the proliferation of conspiracy theories, specifically QAnon, to determine how the media environment, including various media channels, audiences, and messages, played a factor in the group’s growth. QAnon grew from a relatively obscure branch of the alt-right movement into a mob capable of storming the Capitol Building in early 2021. Applying media ecology framework to the QAnon phenomenon, this research investigates the media environment where QAnon was facilitated by using a content analysis of various media surrounding QAnon and those affected by its messages. As a case study, this study reviews comments made about QAnon by Georgia Representative Marjorie Taylor Greene to illustrate the group’s influence and reach. This study demonstrates that media technology aided QAnon in spreading their conspiracy theories through social media influencers, algorithms, word of mouth, and traditional media. The target audiences of QAnon found in this study included people seeking entertainment and people seeking something bigger than themselves. According to this research, the media environment enabled QAnon to reach its audience. Marjorie Taylor Greene is an example of how fringe beliefs influence an individual with rising political authority due to the media environment surrounding her. Lastly, this research illustrates that limitless information and technology are insufficient resources to combat the spread of conspiracy theories such as QAnon due to their essence being epistemological and inherently part of the human condition.
Introduction 1 -- Theoretical Foundation 1 -- Research Questions 2 -- Literature Review 2 -- Conspiracy Theories 2 -- QAnon 8 -- Methodology 11 -- Analysis 16 -- Conclusion 29 -- References 32
Keywords: Academic theses; Communication; Conspiracy theories; Mass media; Social epistemology; Social media